2003 Handbook of Employment Regulations Affecting Florida Farm Employers and Workers: Unemployment Compensation [Federal and State] - Leo C. Polopolus; Michael T. Olexa; Fritz Roka; Carol Fountain (EDIS)
The Unemployment Compensation program is intended to benefit persons unemployed through no fault of their own. This is EDIS document FE420, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published July 2003. This information is included in Circular 1200, Handbook of Employment Regulations Affecting Florida Farm Employers and Workers.